The Withdrawal Time of The Antibiotic of Zinc Bacitracin towards Its Residue in Broiler - Andy Andy; L. Agustina; A. Mujnisa (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
Genetic development of broiler is growing rapidly. Nowadays, broiler is slaughtered at the ages of 29 days rather than 35 days. Rapid growth is usually coupled by an immune deficiencies of broiler, therefore such feed additives as antibiotics is necessary to promote growth and improve endurance of the broiler. The purpose of this research was to investigate the amount of residue of Zinc bacitracin antibiotics in the thigh meat, breast meat, liver, and kidney of the broilers; and to determine the withdrawal time between the discontinuation of the antibiotic of the Zinc bacitracin and the slaughter of the broiler to eliminate or to reduce that residue so that the product of the broiler was safe for human consumption. The research was conducted at Sekolah Tinggi Penyuluhan Pertanian (STPP) Gowa. The broilers used in this study was strain Cobb SR 707, aged 29 days (unsexed), and were obtained from the local broiler farm. The ration containing the antibiotics of the Zinc bacitracin was terminated at day 0, 3, 6, and 9 before slaughtering. The bacteria used to test the dilution sensitivity was Staphylococcus aureus (105-108 colony mL-1). The transmittance reading of the sample solution from the Spectrophotometer was inputted into standard curve generated by from pure antibiotics to determine the antibiotics residue in the samples. The results were then compared with the value of SNI Number: 01-6366-2000 of year 2000. The data were analyzed descriptively and with a non linier regression analysis. The results revealed that the level of the Zinc bacitracin residue decreased following the duration of the cessation of the Zinc bacitracin antibiotic treatment. The antibiotic residue in the sample was smaller than that set in the standards (SNI, 2000) so that the broiler products were safe for human consumption.